THE ROLE OF CAREER DEVELOPMENT TOOLS IN ENHANCING PROACTIVE BEHAVIOR - Ismail, Azman; Mohd Nowalid, Wan Aishah Wan (KINERJA, 2018)
This study aims at measuring the relationship between career development tools and proactive behaviour using self-report questionnaires collected from workers at an oil and gas service company in Peninsular Malaysia. The results of linear regression analysis displayed two major findings: first, job autonomy was positively and significantly related to proactive behaviour. Second, transformational leadership was positively and significantly related to proactive behaviour. In overall, this result demonstrates that the career development tools act as an important predictor of employees’ proactive behavior in the organizational sample. Further, this study provides discussion, implications and conclusion.Keywords: Career Development Tools, Proactive Behavior, Malaysia, SPSS